Struktur Mikroskopis Hati Ikan Seurukan (Osteochilus vittatus) dari Sungai Krueng Sabee Kabupaten Aceh Jaya yang Tercemar Limbah Penggilingan Bijih Emas - Widya Sari; Intan Wulan Okavia; Ria Ceriana; Sunarti Sunarti (Universitas Islam Negeri Ar-Raniry, 2016)
This research is to observe the Seurukan (Osteochilus vittatus) fish liver microscopic structure in Krueng Sabee river, Aceh Jaya Regency. Fish and river water samples were taken from May to June 2015. Histological techniques and research parameters was conducted in FMIPA Microtechnic Laboratory, Syiah Kuala University, while river water and Seurukan fish mercury level was analyzed in Balai Riset dan Standarisasi Industri, Banda Aceh. Completely Randomized Design was applied of the research with three treatments. The treatments were location of fish sample taken through the lenght of Krueng Sabee river that were Panggong village (location I), Paya Seumantok village (location II), and Mon Mata village (location III). Each treatment consisted of six repetition (six fishes). Microscopic structure of Seurukan fish liver was observed with paraffin method histological techniques. The parameters calculated were amount of fish hepatocytes with degeneration and necrose. The data was analyzed using Analysis of Variance followed by Tukey's test. Mercury level of river water in location I is 0,0001047 ppm, location II and III are